Prevalence of self-reported symptoms compatible with Carpal Tunnel Syndrome (CTS) among employees at a neonatal intensive care unit: a cross-sectional study / Prevalenza di sintomi compatibili con la Sindrome del Tunnel Carpale (STC) tra gli operatori di una unità di terapia intensiva neonatale: uno studio trasversale - Tsovili, E.; Rachiotis, G.; Touche, S. (La Medicina del Lavoro, 2012)
Summary Background: Carpal Tunnel Syndrome is a significant work-related disease. Objective: The aim of the study was to investigate the prevalence of symptoms possibly related to CTS in workers in a neonatal intensive care unit. Methods: The self-administered INRS questionnaire for musculoskeletal symptoms was distributed to all 41 employees of a neonatal intensive care unit and to an appropriate sample of 82 employees of a paediatric emergency department and an adult intensive care unit. Results: Employees of the neonatal intensive care unit recorded a significantly higher prevalence of symptoms potentially related to CTS in comparison with the reference group (58.5% vs 8.3%, respectively; p<0.001). Logistic regression analysis indicated that work in the neonatal intensive care unit was independently associated with the risk of symptoms potentially related to CTS. Conclusions: The results provide some evidence for a higher prevalence of symptoms potentially related to CTS in nursing personnel of a neonatal intensive care unit. Further research work is needed to prove a causal association. Riassunto «Prevalenza di sintomi compatibili con la Sindrome del Tunnel Carpale (STC) tra gli operatori di una unità di terapia intensiva neonatale: uno studio trasversale». Obiettivo: Scopo dello studio è stato quello di valutare la prevalenza di sintomi potenzialmente correlati con la Sindrome del Tunnel Carpale (STC) in lavoratori di un’ unità di terapia intensiva neonatale e della sua possibile associazione con fattori di rischio. Metodo: è stato somministrato un questionario per i sintomi muscolo-scheletrici a tutti i 41 operatori di una unità di terapia intensiva neonatale e ad un adeguato campione di 82 operatori del reparto di emergenza pediatrica e rianimazione adulti. Risultati: i lavoratori dell’unità di terapia intensiva neonatale hanno deposto una prevalenza significativamente maggiore di sintomi della sindrome del tunnel carpale in confronto al gruppo di riferimento (58,5% vs 8,3%, p<0,001). L’analisi di regressione logistica ha indicato che lavorare in un’unità di terapia intensiva neonatale è indipendentemente associato con il rischio di sintomi potenzialmente correlati con STC. I risultati depongono per l’evidenza di una maggiore prevalenza di sintomi potenzialmente correlati con STC tra i lavoratori di una unità di terapia intensiva neonatale: Ulteriori indagini sono necessarie per dimostrare l’esistenza di una associazione causale.